(untitled) - Guifoyle, Andrew (Thành phố Hồ Chí Minh, 2013)
In Academic Task 1 of the Writing module, you are expected to write a short descriptive report based on visual information or data. This visual information is most commonly presented as line and bar graphs, pie charts or tables.
Keywords: English language,Ngôn ngữ Anh; Writing,Viết